Pengaruh Aksesoris dan Elemen Pembentuk Ruang terhadap Suasana dan Karakter Interior Lobi Hotel Artotel Surabaya - Ayhwien Chressetianto (Intra, 2013)
Space is a place where one interacting delivers action and reaction. Human reaction can arise from the influence of the State of the environment. The circumstances surrounding the perimeter of the environment/translated into design elements that can satisfy the needs of physical and spiritual exercises to the user, also called the atmosphere. Influence of atmosphere not only comes from the presence of the elements composing spaces but other elements such as room accessories. Accessories in a space that is often thought of as a decorative element, it gives impact to influence the emotions of visitors which ultimately impact on the atmosphere of the space. The atmosphere and character of the spaces formed by the influence of the elements composing spaces and accessories, among other things, a quiet space character produces a cheerful character, resulting in a deeply relaxed atmosphere that inspires creativity, familiar characters produce a family atmosphere, and earthy character generates an atmosphere of simple spaces. The character and atmosphere of that form are linked and tagged for compliance with the style/function area on the site.